Anti-Ro/SSA and anti-La/SSB autoantibodies in the tear fluid of patients with Sjogren's syndrome - TOKER, AYŞE EBRU; DİRESKENELİ, RAFİ HANER (BMJ PUBLISHING GROUP, 2004)
Purpose: To investigate the presence of anti-Ro/SSA and anti-La/SSB antibodies in the tear fluid and serum of patients with Sjogren's syndrome and to evaluate the association of these autoantibodies with the severity of keratoconjunctivitis sicca. Methods: Tear fluid and serum were obtained from 28 patients with Sjogren's syndrome and 17 age matched normal control subjects. Evaluation of tear fluid and sera anti-Ro/SSA and anti-La/SSB levels was done by using a quantitative enzyme linked immunosorbent assay kit designed for the quantitative measurement of IgG class autoantibodies directed against highly purified SSA and SSB antigens. Tear function and ocular surface were evaluated by Schirmer I test, tear break up time, and rose bengal staining. Dry eye symptom scores were recorded. Results: Increased levels of anti-Ro/ SSA and anti-La/SSB antibodies were detected in sera of 57.1% and 50% of SS patients, respectively. Six patients had increased levels of anti- Ro/ SSA in the tear fluid, in one case anti- Ro/ SSA being detected in tear fluid when it was negative in serum. Ten patients had positive anti- La/SSB titres in tear fluid and in four of these patients, anti- La/SSB titres were not elevated in serum. A positive correlation was observed between serum and tear fluid titres of anti- Ro/ SSA ( r = 0.43, p = 0.02), but not of anti- La/SSB. Serum anti- Ro/ SSA and anti- La/SSB concentrations correlated positively with dry eye symptom scores ( r = 0.42, p = 0.02 and r = 0.48, p = 0.01, respectively) and negatively correlated with Schirmer I test scores ( r = 20.39, p = 0.04 and r = 20.40, p = 0.03, respectively). Significant correlations were found between tear anti- La/SSB concentrations and dry eye symptom score ( r = 0.56, p = 0.02) and also rose bengal staining scores of the ocular surface ( r = 0.44, p = 0.02). Conclusion: This study shows that autoantibodies against Ro/ SSA and La/SSB antigens are present in the tear fluid of some patients with SS and their presence in serum or tear fluid is associated with the severity of keratoconjunctivitis sicca. Additional measurement of tear fluid levels of anti- Ro/ SSA and anti- La/SSB may serve as a valuable diagnostic indicator of SS.
Keywords: RNA POLYMERASE-III; 5S RIBOSOMAL-RNA; SS-A/RO; CYTOPLASMIC RIBONUCLEOPROTEINS; RO RIBONUCLEOPROTEINS; SALIVARY-GLANDS; 52-KD PROTEIN; ANTIBODIES; ASSOCIATION; 60-KD